Tafsir Surat al-Ahzab 56: Variety, Meaning and Practice of Shalawat in the Archipelago - Erwanto, Dian; Athaillah, Muhammad (Al-Karim: International Journal of Quranic and Islamic Studies, 2023)
This study examines the practice of Shalawat within the cultural context of the Nusantara through an analysis of Surah al-Ahzab verse 56. Shalawat, as a form of praise for Prophet Muhammad (peace be upon him), is deeply embedded in the religious life of Muslim communities worldwide, including in the Nusantara region. The interpretation of Surah al-Ahzab verse 56 serves as a fundamental reference in understanding the significance of Shalawat in Islam. Employing a methodological approach that combines literature analysis, cultural context understanding, and a review of both classical and contemporary interpretations, this study explores the Quranic interpretation of Shalawat from theological (aqidah), jurisprudential (fiqh), and Sufi (tasawuf) perspectives. Furthermore, this research investigates the operationalization and implications of Shalawat practices in Indonesia, considering their ideological, traditional, and spiritual dimensions. The findings reveal that Shalawat in the Nusantara manifests in diverse forms, both theoretically and pragmatically, in alignment with the Quranic command. By analyzing Surah al-Ahzab verse 56 through three distinct scholarly perspectives, this study provides a comprehensive understanding of Shalawat in Nusantara culture. Ultimately, this research highlights the role of Quranic interpretation in shaping the perception and practice of Shalawat, reinforcing its relevance within the Indonesian cultural and religious landscape. Contribution: This study contributes to the understanding of Shalawat in Nusantara culture by demonstrating how Quranic interpretation, through theological, jurisprudential, and Sufi perspectives, shapes its practice and significance within the Indonesian religious landscape.